ANALYSIS OF WORKING SPACE DAYLIGHT ILLUMINATION AT COFFEE SHOP "GOOD DANK" IN MALANG CITY (International Conference of Graduate School on Sustainability (ICGSS), 2020)
The phenomenon of the rise of coffee shops in Malang, which is growing at around 20% per year, has presented various contemporary architectural forms of various styles. Its presence aims to provide appreciation and comfort to the audience. The appearance of the façade and interior design and workspace emphasizes eclectic design experimentation. The problem is that the daylighting aspect of these facilities is often under-considered. Even though these factors, mainly the reflectivity factor of objects in the room and outside factors such as the light of the celestial ball, greatly affect the level of comfort in a room or building. The purpose of this study is to evaluate the level of daylight illumination from the workspace with the case at the “Good Dank” coffee shop in Malang City. The method of analysis uses an explanatory research approach in a descriptive inductive manner. Based on observations, the illumination level of the coffee shop that is the object of the study has not reached 250 lux. This means that the workspace at the “Good Dank” coffee shop has not met the requirements required for visual comfort following the Indonesian National Standard (SNI) for tropical buildings in Indonesia. Keywords: daylight, illumination, workspace, coffee shop.